Advertisement Remove all ads

Simplify: ( 2 − 1 + 3 − 1 ) − 1 - Mathematics

Sum

Simplify:

\[\left( 2^{- 1} + 3^{- 1} \right)^{- 1}\]
Advertisement Remove all ads

Solution

\[\left( 2^{- 1} + 3^{- 1} \right)^{- 1} = \left( \frac{1}{2} + \frac{1}{3} \right)^{- 1} {\to (a}^{- 1} = 1/a) \]
\[ = \left( \frac{5}{6} \right)^{- 1} = \frac{6}{5} {\to (a}^{- 1} = 1/a)\]

 

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

RD Sharma Class 8 Maths
Chapter 2 Powers
Exercise 2.2 | Q 4.3 | Page 18
Advertisement Remove all ads

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×